Governance, Sovereignty and Globalisation - Keith, Kenneth J (Victoria University of Wellington Law Review, 1998)
The 5th Biennial Conference of the NZ Council of Trade Unions had as its main theme "The Next Decade - Te Takau Heke Iho". In his address to that conference Sir Kenneth Keith spoke about the end of democracy and of the nation state. Sir Kenneth discussed the role of international law in globalisation, and the transformation of the organisation of public powers. Key areas of international activity were examined and options for regulation were proposed, including public and private regulation. Sir Kenneth noted the need for greater dissemination of information on international rules and treaties, including public involvement during treaty negotiation. Finally, Sir Kenneth discussed implementation concluding that a mixture of national and international methods of implementation may be most appropriate. The speech is reproduced here.